1997
DOI: 10.2190/j309-ejmx-whrm-4uyg
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Late Life Depression: A Guide for the Primary Care Physician

Abstract: It is important to be vigilant for the variety of depressive presentations that occur in older primary care patients. Neurological causes of depression (such as stroke), suicide, and a longer time to recovery are all more frequent concerns in older depressed patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In agreement with previous studies [4,9,12], the presence of single medical conditions was found to be strongly associated with depression. The relative strength of the relationship, however, tended to differ by the type of medical conditions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous studies [4,9,12], the presence of single medical conditions was found to be strongly associated with depression. The relative strength of the relationship, however, tended to differ by the type of medical conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Older people with depressive symptoms are more likely to have a negative view of their health [7,8]. Depression in later life is also known to be associated with increased morbidity, functional impairment, mortality, and health services use [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…6 It has begun to receive increasing research attention, 161,163-167 but further results are needed before definitive conclusions can be drawn. 6 It has begun to receive increasing research attention, 161,163-167 but further results are needed before definitive conclusions can be drawn.…”
Section: Combined and Sequential Drug And Nondrug Treatmentsmentioning
confidence: 99%
“…Depression causes deterioration in social functioning and quality of life, and is also related to an increase in diseases in the elderly (Conn and Steingart, 1997;Fried et al, 1998). Thus, it is important to detect depression in the elderly and to treat it promptly.…”
Section: Introductionmentioning
confidence: 99%